Life satisfaction, ethnicity and neighbourhoods: Is there an effect of neighbourhood ethnic composition on life satisfaction? - Gundi Knies; Alita Nandi; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Using a rich, nationally representative data set with a large sample of minorities and matched small area characteristics, we explore differences in life satisfaction for ethnic groups living in UK. We test the hypothesis that minorities will be less satisfied, which will in part be explained by less favourable individual and area contexts, but that living in areas with a larger proportion of own ethnic group promotes well-being. We find that satisfaction is lower among minorities, ceteris paribus, but area concentration is associated with higher life satisfaction for certain groups. We discuss the implications of our findings.
Keywords: I31; J15; R23; O15; 330; Life Satisfaction; Happiness; Ethnic group; Neighbourhood; Subjective well-being; UKHLS